2022
DOI: 10.1371/journal.pone.0273828
|View full text |Cite
|
Sign up to set email alerts
|

Use of explicit priming to phenotype absolute pitch ability

Abstract: Musicians with absolute pitch (AP) can name the pitch of a musical note in isolation. Expression of this unusual ability is thought to be influenced by heritability, early music training and current practice. However, our understanding of factors shaping its expression is hampered by testing and scoring methods that treat AP as dichotomous. These fail to capture the observed variability in pitch-naming accuracy among reported AP possessors. The aim of this study was to trial a novel explicit priming paradigm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…In line with this argumentation is a neuroimaging study of gap detection tasks (Vaden et al, 2020) that reported a lack of activation of brain regions belonging to the ventral stream, such as the planum polare (Kim and Knösche, 2017b). However, considering that gap detection was able to predict pitch identification in the regression analyzes and that the approach to AP as a continuum trait is more suitable for the scoring method used in this investigation (Germano et al, 2021;Bairnsfather et al, 2022b), these results are most likely due to the inability of the arbitrary criteria used for the group assignment to generate clearly distinct groups. Aware of such limitation, we conducted correlation and regression analyzes between the measures of pitch identification and GIN tests, showing that gap detection explained a high amount of the variance (between 20 and 36%, considering the values of adjusted R 2 for the uncontrolled models) present in our sample's pitch identification ability.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In line with this argumentation is a neuroimaging study of gap detection tasks (Vaden et al, 2020) that reported a lack of activation of brain regions belonging to the ventral stream, such as the planum polare (Kim and Knösche, 2017b). However, considering that gap detection was able to predict pitch identification in the regression analyzes and that the approach to AP as a continuum trait is more suitable for the scoring method used in this investigation (Germano et al, 2021;Bairnsfather et al, 2022b), these results are most likely due to the inability of the arbitrary criteria used for the group assignment to generate clearly distinct groups. Aware of such limitation, we conducted correlation and regression analyzes between the measures of pitch identification and GIN tests, showing that gap detection explained a high amount of the variance (between 20 and 36%, considering the values of adjusted R 2 for the uncontrolled models) present in our sample's pitch identification ability.…”
Section: Discussionmentioning
confidence: 55%
“…In line with this argumentation is a neuroimaging study of gap detection tasks ( Vaden et al, 2020 ) that reported a lack of activation of brain regions belonging to the ventral stream, such as the planum polare ( Kim and Knösche, 2017b ). However, considering that gap detection was able to predict pitch identification in the regression analyzes and that the approach to AP as a continuum trait is more suitable for the scoring method used in this investigation ( Germano et al, 2021 ; Bairnsfather et al, 2022b ), these results are most likely due to the inability of the arbitrary criteria used for the group assignment to generate clearly distinct groups.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation